(untitled) (BERBAKTI : Jurnal Pengabdian Kepada Masyarakat, 2024)
Young mothers in Pacar Peluk Village are almost average housewives who do not have a profession outside the home. Based on this, the PKM Team in coordination with the village government and the head of the pacarpeluk village PKK is interested in providing assistance and introduction to mothers in pacarpeluk village to be creative and change healthy lifestyles for families. This activity has the following objectives: Provide training and introduction to microgreen for PKK mothers in Pacarpeluk Village. The PKM approach with Participatory Action Research (PAR) is an approach whose process aims at learning to solve problems and fulfil the practical needs of the community, as well as science, and the process of changing understanding of microgreen learning and training. With the implementation of microgreen introduction and training activities, PKK mothers will understand that microgreen in addition to being rich in nutrients obtained from plants, PKK mothers also know more about the stages of planting using the microgreen system which requires a relatively short time so that it is suitable for the health needs of Pacarpeluk village families.